The Sarbanes-Oxley act from a legislative viewpoint. (2nd January 2016) - Kecskés, András
ABSTRACT: This paper examines the Sarbanes-Oxley Act of 2002, a rather contested and criticised Act, mainly from a legisprudence perspective. During the course of the analysis, an outline of the legislative process will be given while also considering the intended and the unintended consequences. The importance of the Act is manifold. On one hand, it is a milestone in corporate governance within the USA. It enjoyed an almost unprecedented bipartisan support due to corporate scandals erupting in the early 2000s. Moreover, the Act itself is not only effective within the United States, but also affects publicly listed companies worldwide that are listed on American stock exchanges. Unfortunately, the Act itself was created in a hurry, which greatly affected the overall quality. The main idea is to showcase some of the dangers of politically overloaded legislation by recounting the legislative process of the Sarbanes-Oxley Act.